Zinc Homeostasis in Platelet-Related Diseases - Mammadova-Bach, Elmina (Int J Mol Sci, 2019)
Zn(2+) deficiency in the human population is frequent in underdeveloped countries. Worldwide, approximatively 2 billion people consume Zn(2+)-deficient diets, accounting for 1–4% of deaths each year, mainly in infants with a compromised immune system. Depending on the severity of Zn(2+) deficiency, clinical symptoms are associated with impaired wound healing, alopecia, diarrhea, poor growth, dysfunction of the immune and nervous system with congenital abnormalities and bleeding disorders. Poor nutritional Zn(2+) status in patients with metastatic squamous cell carcinoma or with advanced non-Hodgkin lymphoma, was accompanied by cutaneous bleeding and platelet dysfunction. Forcing Zn(2+) uptake in the gut using different nutritional supplementation of Zn(2+) could ameliorate many of these pathological symptoms in humans. Feeding adult rodents with a low Zn(2+) diet caused poor platelet aggregation and increased bleeding tendency, thereby attracting great scientific interest in investigating the role of Zn(2+) in hemostasis. Storage protein metallothionein maintains or releases Zn(2+) in the cytoplasm, and the dynamic change of this cytoplasmic Zn(2+) pool is regulated by the redox status of the cell. An increase of labile Zn(2+) pool can be toxic for the cells, and therefore cytoplasmic Zn(2+) levels are tightly regulated by several Zn(2+) transporters located on the cell surface and also on the intracellular membrane of Zn(2+) storage organelles, such as secretory vesicles, endoplasmic reticulum or Golgi apparatus. Although Zn(2+) is a critical cofactor for more than 2000 transcription factors and 300 enzymes, regulating cell differentiation, proliferation, and basic metabolic functions of the cells, the molecular mechanisms of Zn(2+) transport and the physiological role of Zn(2+) store in megakaryocyte and platelet function remain elusive. In this review, we summarize the contribution of extracellular or intracellular Zn(2+) to megakaryocyte and platelet function and discuss the consequences of dysregulated Zn(2+) homeostasis in platelet-related diseases by focusing on thrombosis, ischemic stroke and storage pool diseases.